Novel Bivalent mRNA‐LNP Vaccine for Highly Effective Protection against Pneumonic Plague - Uri Elia; Yinon Levy; Hila Cohen; Ayelet Zauberman; David Gur; Inbal Hazan‐Halevy; Moshe Aftalion; Shani Benarroch; Erez Bar‐Haim; Orit Redy‐Keisar; Ofer Cohen; Dan Peer; et al. (Advanced Science)
Abstract Yersinia pestis, the causative agent of plague, remains a significant global health hazard and a potential top‐tier biothreat despite modern medical advances. Here, two mRNA constructs encoding different versions of the low‐calcium response virulence (LcrV) protective antigen, an essential virulence factor of Y. pestis, are designed and evaluated. Next, the immunogenicity and protective efficacy both independently and in combination is assessed with the previously reported F1‐encoding mRNA construct in the well‐established mouse model of pneumonic plague. The findings reveal that human Fc‐conjugated F1 + LcrV combination mRNA vaccination resulted in significant immune activation and substantial protection against intranasal Y. pestis challenge. Notably, the combined vaccine demonstrates protective efficacy against two highly virulent wild‐type Y. pestis strains representing distinct biovars and an atypical, unencapsulated strain. This study represents the first comprehensive evaluation of mRNA constructs encoding innovatively designed versions of LcrV and F1 for pneumonic plague prevention, addressing critical gaps in current vaccination approaches. This study establishes the mRNA‐lipid nanoparticle (LNP) platform as a promising tool for addressing bacterial pathogens, including those resistant to antibiotics. By broadening its applicability to diverse threats, this technology represents an innovative approach to tackling some of the most pressing challenges in global health.